A Multi-Objective Optimization Technique to Develop Protection Systems of Distribution Networks with Distributed Generation - Pereira, Katiani (2018)
This paper presents a new methodology based on multi-objective optimization techniques to perform an optimized, coordinated and selective allocation of control and protection devices in distribution networks with distributed generation (DG). The proposed mathematical model consists of two objective functions that consider economic issues and the network continuity index. Physical and operational constraints are taken into account, with emphasis on the set of constraints based on practical rules of distribution companies and international technical standards, which require the specification, coordination and selectivity of the protection devices installed in the network. The possibility of load transfer from neighboring feeders and islanded DG operation is also considered. The proposed model is a mixed integer non-linear programming and we use NSGA-II (Nondominated Sorting Genetic Algorithm) to solve it. The proposed methodology is applied in a real 135-bus system found in literature.